Comparison of skin effects of immediate treatment modalities in experimentally induced hydrofluoric acid skin burns. Issue 6 (29th January 2014) - Songur, Meltem K; Akdemir, Ovunc; Lineaweaver, William C; Cavusoglu, Turker; Ozsarac, Murat; Aktug, Huseyin; Songur, Ecmel; Tiftikcioglu, Yigit O
Abstract: Hydrofluoric acid (HF) burns cause immediate damage and painful long‐term sequellae. Traditionally, chelating agents have been used as the initial treatment for such burns. We have introduced epidermal growth factor (EGF) into an HF model to compare EGF with Ca 2+ and Mg 2+ treatments; 40 Sprague Dawley rats were divided into five groups. Each rat suffered a 6 × 4 cm 2 burn induced by 40% HF. Group 1 had no treatment, group 2 had saline injected beneath the burn, group 3 received magnesium sulphate injections, group 4 received calcium gluconate and group 5 received EGF. Specimens were evaluated via planimetry and biopsy at intervals of 4, 8, 24 and 72 hours. Fluid losses were significantly less in the Mg 2+ and EGF groups. The EGF group had the smallest burn area, least oedema, least polymorphonuclear granulocyte (PMN) infiltration, most angiogenesis and highest fibroblast proliferation of any group ( P < 0·005). EGF limited HF damage morphologically and histologically more effectively than Ca 2+ or Mg 2+ . This finding indicates that HF treatment via growth factors may be an improvement over chelation therapy.